Industrial training among Students of Faculty of Pharmacy UiTM Puncak Alam: Bridging theory and practice / Muhammad 'Izzuddin Zamery - Zamery, Muhammad 'Izzuddin (Faculty of Pharmacy, 2023)
In an increasingly competitive job market, practical experience is a valuable asset that sets graduates apart. Recognizing this, the Faculty of Pharmacy at UiTM Puncak Alam has embarked on an Industrial Training Program that not only enriches students' academic journey but also bridges the gap between theoretical knowledge and real-world application. A Glimpse into the Latest PHC672 Course: Under the course code PHC672, the Industrial Attachment Program is a credit-bearing endeavor that spans over 6 weeks, from August 14 to September 22, 2023. This initiative involves 174 students from the third-year Bachelor of Pharmacy program, each embarking on a journey to gain invaluable experience in diverse sectors of the pharmaceutical industry.